2004
DOI: 10.1529/biophysj.104.046193
|View full text |Cite
|
Sign up to set email alerts
|

Phase Resetting and Phase Locking in Hybrid Circuits of One Model and One Biological Neuron

Abstract: To determine why elements of central pattern generators phase lock in a particular pattern under some conditions but not others, we tested a theoretical pattern prediction method. The method is based on the tabulated open loop pulsatile interactions of bursting neurons on a cycle-by-cycle basis and was tested in closed loop hybrid circuits composed of one bursting biological neuron and one bursting model neuron coupled using the dynamic clamp. A total of 164 hybrid networks were formed by varying the synaptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
139
0
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 48 publications
4
139
0
1
Order By: Relevance
“…Previously, we showed that our theoretical methods predict 1:1 modes of phase-locking robustly, where 161 of 164 networks were predicted correctly (Oprisan et al 2004). In contrast to the uniform success we experienced with inhibitory circuits, a significant fraction of the hybrid circuits constructed with excitation suffered from prediction failures.…”
Section: Systematic Prediction Failures Observed For Excitation But Nmentioning
confidence: 74%
See 4 more Smart Citations
“…Previously, we showed that our theoretical methods predict 1:1 modes of phase-locking robustly, where 161 of 164 networks were predicted correctly (Oprisan et al 2004). In contrast to the uniform success we experienced with inhibitory circuits, a significant fraction of the hybrid circuits constructed with excitation suffered from prediction failures.…”
Section: Systematic Prediction Failures Observed For Excitation But Nmentioning
confidence: 74%
“…This framework was used to derive a discrete map for the time evolution of the system on a cycle-to-cycle basis. (Figure adapted from Oprisan et al 2004. ) interval of the current cycle and the effect of F2 is localized to the ts interval of the next cycle.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 3 more Smart Citations